2018
DOI: 10.1021/acsnano.7b08718
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Transport in Quasi-1D van der Waals Crystal Ta2Pd3Se8 Nanowires: Size and Length Dependence

Abstract: Van der Waals (vdW) crystals with covalently bonded building blocks assembled together through vdW interactions have attracted tremendous attention recently because of their interesting properties and promising applications. Compared to the explosive research on two-dimensional (2D) vdW materials, quasi-one-dimensional (quasi-1D) vdW crystals have received considerably less attention, while they also present rich physics and engineering implications. Here we report on the thermal conductivity of exfoliated qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 55 publications
0
66
0
Order By: Relevance
“…The fully ballistic heat conduction implies that the thermal conductance (K) of a nanostructure is independent of the structure length (L), thus the thermal conductivity (κ  K × L) loses its meaning as a material property and becomes merely proportional to the length. Such a lengthdependent thermal conductivity was experimentally observed at room temperature in silicon films 5 and membranes 6 , SiGe and Ta2Pb3Se8 nanowires (NWs) [7][8][9] , and suspended graphene 10,11 . However, Chang with colleagues argued 7,8,12 that the thermal conductivity may depend on the length due to the thermal contact resistance, even if heat conduction is purely diffusive.…”
Section: Introductionmentioning
confidence: 76%
“…The fully ballistic heat conduction implies that the thermal conductance (K) of a nanostructure is independent of the structure length (L), thus the thermal conductivity (κ  K × L) loses its meaning as a material property and becomes merely proportional to the length. Such a lengthdependent thermal conductivity was experimentally observed at room temperature in silicon films 5 and membranes 6 , SiGe and Ta2Pb3Se8 nanowires (NWs) [7][8][9] , and suspended graphene 10,11 . However, Chang with colleagues argued 7,8,12 that the thermal conductivity may depend on the length due to the thermal contact resistance, even if heat conduction is purely diffusive.…”
Section: Introductionmentioning
confidence: 76%
“…10 In this work, we only focus on thermal transport in infinite-length 1D ultrathin carbon nanostructures. The previous studies indicate that thermal transports in finitelength 1D nanostructures [48,49] and bulk van der Waals nanowires [50] possess different transport phenomena with those in infinite-length 1D nanostructures. Thus, based on our results, it is worth studying length-dependent thermal transport in finitelength 1D nanostructures and transport issues in bulk crystal made of van der Waals carbon nanowires in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Though free‐standing single‐atom chains have not been obtained, some quasi‐1D van der Waals (quasi‐1D vdW) crystals which are the assembling of atomic thin 1D covalently bonded building blocks by van der Waals forces have been studied in some transition metal chalcogenides. Li et al studied the thermal transport in quasi‐1D vdW Ta 2 Pd 3 Se 8 nanorod, and found that the measured thermal conductivity was still greatly influenced by the cross‐sectional sizes, in spite of that the interchain vdW interactions are much less than the interatomic interactions along molecular chains. Tang et al have demonstrated that using quasi‐1D vdW Sb 2 Se 3 nanocrystals in solar cells has an unparalleled advantage: no surface passivation layer is required to reduce the recombination of exciton since there are no dangling bonds in quasi‐1D vdW Sb 2 Se 3 nanocrystals.…”
Section: Atomic Chainsmentioning
confidence: 99%